Pelatihan Es Krim Sehat dan Bergizi Bagi Ibu-Ibu PKK untuk Meningkatkan Nilai Gizi Keluarga Serta Peluang Wirausaha Rumah Tangga di Kota Samarinda - I Wayan Sudarmayasa; Krishna Anugrah; Kristian Triatmaja Raharja (Samarinda State Polytechnic, 2019)
We can rule the role of mothers today out for their role in domestic life. Mothers have been able to sustain family sustainability, especially in the economic field. Mothers can only wait at home and stand by and wait for their husbands, but they can play a greater role in supporting the economic needs of their families. But the question is whether mothers already have the skills to help support their family's economic needs? Based on this background, the authors conducted skills training for mothers, especially those who joined the PKK group by teaching ice cream making skills. In this article, we will discuss the training that will be given starting with the basic introduction, equipment, processing, packaging process so that they can sell to get profits for them. The training that takes place in the Ketupat Samarinda village across from this can later be expected by the mothers after the training will have the skills and can apply it at home so that it can help the family economy